A novel salt-free ruthenium-catalyzed alkylation of aryl amines - Hollmann, Dirk; Bähn, Sebastian; Tillack, Annegret; Parton, Rudy; Altink, Rinke; Beller, Matthias (Tetrahedron letters, 2008)
For the first time the alkylation of aryl amines using cyclic amines, for example, pyrrolidine is described. This novel reaction proceeds without the need of external hydrogen or pressure under ambient conditions in the presence of the Shvo catalyst. The alkylation of aryl amines using cyclic amines such as pyrrolidine proceeds via borrowing hydrogen methodology in the presence of 1 mol % Shvo catalyst. During the reaction multiple carbon–nitrogen cleavage and formation occurred. This novel reaction sequence leads to N-aryl-pyrrolidines and -piperidines.